Time of others : Catalogue. - Azusa, Hashimoto; Museum of Contemporary Art Tokyo, Tokyo; The National Museum of Art, Osaka; Singapore Art Museum, Singapore; Queensland Art Gallery, Brisbane; Juri, Murakami; Meiko, Sano; Yasuko, Furuichi (Tokyo : Museum of Contemporary Art Tokyo, 2015)
Bunoan, Ringo ; Chieh-jen, Chen ; Chong, Heman ; Dalena, Kiri ; Fletcher, Graham ; Tzu Nyen, Ho ; Husein, Saleh ; Jones, Jonathan ; Tsubasa, Kato ; Kawara, On ; Beom, Kim ; Lê, An-My ; Minouk, Lim ; Mahmood, Basir ; mamoru ; Futoshi, Miyagi ; Pak, Tozer ; Phinthong, Pratchaya ; Quek, Bruce ; ruangrupa ; Motoyuki, Shitamichi ; Utarit, Natee ; Rattana, Vandy ; An Khánh, Võ ; Vo, Danh
Time of others, Museum of Contemporary Art Tokyo, Tokyo, 11/04-28/06/2015 // The National Museum of Art, Osaka, 25/07-23/09/2015 // Singapore Art Museum, Singapore, 19/11/2015-28/02/2016 // Queensland Art Gallery, Brisbane, 11/06-18/09/2016
boek